Kelimpahan Kepik Predator (Hemiptera: Reduviidae) di Daerah Endemik Serangan Ulat Api Pada Perkebunan Kelapa Sawit Rakyat - Siska chiko efendi; Yaherwandi Yaherwandi; Maiwil Diratika (Jurnal Penelitian Pertanian Terapan, 2020)
Caterpillar fire is classified as the main pests in oil palm plants and are found in almost all oil palm plantations in Indonesia. The caterpillar fire control is currently being directed to biological control by predatory insects. Insects from the Reduviidae family are one of the insects whose members are predators of caterpillar fire. This study aims to (1) identify predatory ladybug species (Hemiptera: Reduviidae) found in endemic areas of caterpillar fire attacks. (2) studying the abundance of predatory ladybugs (Hemiptera: Reduviidae) in areas endemic to fire caterpillar attacks. The research locations were Nagari Panyubarangan, Timpeh district, and Nagari Gunung Selasih, Pulau Punjung district. Identification of sample insects was carried out at the insect Bioecology Laboratory, plant protection department, faculty of Agriculture, Andalas University and campus III land and plant laboratory Dharmasraya from April-July 2018. The sampling of insects uses two methods, namely direct collection, and swing net. In this research, 8 species of predatory ladybugs were found. Of these 8 species, only 3 species preyed on caterpillar fire. Species that prey on fire caterpillars have the highest abundance of Cosmolestes practices as many as 116 individuals and followed by 64 individual Zelus regarding species.Â Â